1938
DOI: 10.1152/ajplegacy.1938.123.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Changes With Age in the Renal Function in Adult Men

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

1967
1967
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…At 23 months of age, rats were assigned randomly to drug treatment with the ET A [3] 54 [4] 56 [6] 54 [7] Hematocrit (%) 47 [3] 46 [2] 48 [3] 48 [1] Distribution volume is expressed in absolute values for exogenous creatinine (mL) as fraction of body volume (grams of body weight in mL Figure 3b), and reversed podocyte injury and glomerular basement membrane hypertrophy (Figure 2c and 2d). In aged rats, treatment had no effect on tubulo-interstitial injury (injury score 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 23 months of age, rats were assigned randomly to drug treatment with the ET A [3] 54 [4] 56 [6] 54 [7] Hematocrit (%) 47 [3] 46 [2] 48 [3] 48 [1] Distribution volume is expressed in absolute values for exogenous creatinine (mL) as fraction of body volume (grams of body weight in mL Figure 3b), and reversed podocyte injury and glomerular basement membrane hypertrophy (Figure 2c and 2d). In aged rats, treatment had no effect on tubulo-interstitial injury (injury score 1.…”
Section: Resultsmentioning
confidence: 99%
“…Aging in humans and rodents progressively impairs renal function 1,2 and structure, the latter of which is characterized by damage of podocytes and mesangial matrix, as well as capillary hypertrophy and obliteration resulting in glomerulosclerosis. 2 The exact mechanisms underlying agedependent renal injury are unknown.…”
mentioning
confidence: 99%
“…Its terminal half-life was previously thought to be about 2 h, but recent studies have shown it to range from 27-693 h and nephrotoxicity is associated with abnormal tissue accumulation of the drug (Schentag et al, 1978a). It is also important to take into account the effects of age on renal function (Lewis & Alving, 1938;Davies & Shock, 1950;Rowe etal., 1976).…”
Section: Factors Influencing Nephrotoxicitymentioning
confidence: 99%
“…Yet dehydration is a major health risk for the elderly (5), and the elderly are susceptible to dehydration because of increased fluid losses (41). Aged kidneys have a decreased ability to concentrate urine (17,27) and to conserve sodium (8), along with a relative resistance to vasopressin (25), and release less renin when challenged (6). These changes with age predispose the elderly to hypovolemia and dehydration because of the reduced ability to conserve water and sodium during times of relative water and sodium loss.…”
mentioning
confidence: 99%